Personal Development as a Key Criterion for Higher Education Quality - SLYUSARENKO, Olena; TALANOVA, Zhanneta; DEBYCH, Mariia; LEVKULYCH, Vasyl; SHCHEGLIUK, Dariia (WISDOM, 2022)
Purpose. The study focuses on revealing the significance of personal development as a criterion of higher education quality in order to improve higher education quality and individual self-realization and social development. Theoretical basis. The theoretical and conceptual basis of the study is a set of works in a number of interrelated thematic areas by A. Gehlen, M. Scheler, E. Spranger, V. Kremen, V. Luhovyi, Y. X. Ye, J. Chen, E. Вajramovic, B. Islamović, G. Saglamer, L. Bhandari, S. Kale, S. Cadena, I. Garcia-Serrano, T. Gualli, J. Ortiz, P. Pradeep, М. Taylor, K. Bintan, D. Annamali, M. Muftahu, A. Naji and others. Originality. The authors substantiate the priority of importance of personal development to improve higher education quality. The inconsistency of modern stratagems for the development of higher education and its quality improvement with the needs and requirements of personal development has been revealed, and the significance of personal development as a criterion of higher education quality for improving higher education quality and individual self-realization and social development has been determined. Conclusions. Personal development is imperative to improve higher education quality. The competency paradigm reflects needs for personal development only in part, so it needs to be either supplemented or replaced by an adequate criterion tool.